1996
DOI: 10.1038/hdy.1996.124
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of Anopheles gambiae populations from East and West Africa: comparison of microsatellite and allozyme loci

Abstract: Genetic variation of Anopheles gambiae was analysed to assess interpopulation divergence over a 6000 km distance using short tandem repeat (microsatellite) loci and allozyme loci. Differentiation of populations from Kenya and Senegal measured by allele length variation at five microsatellite loci was compared with estimates calculated from published data on six allozyme loci (Miles, 1978). The average Wright's FST of microsatellite loci (0.016) was lower than that of allozymes (0.036). Slatkin's RST values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
129
2
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(149 citation statements)
references
References 27 publications
(26 reference statements)
16
129
2
2
Order By: Relevance
“…With respect to the paradox of broadly distributed shared haplotypes, it is noteworthy that for each of the four loci, the amount of variation distributed among populations within species was either insignificant (white, tox, 2R arrangements, and xdh) or very minor (G6pd). This finding is consistent with previous mtDNA and microsatellite studies that have suggested shallow population structure (14,29,30). Without well defined geographic population structure, localized introgression events cannot readily be perceived as such (16).…”
Section: Resultssupporting
confidence: 92%
“…With respect to the paradox of broadly distributed shared haplotypes, it is noteworthy that for each of the four loci, the amount of variation distributed among populations within species was either insignificant (white, tox, 2R arrangements, and xdh) or very minor (G6pd). This finding is consistent with previous mtDNA and microsatellite studies that have suggested shallow population structure (14,29,30). Without well defined geographic population structure, localized introgression events cannot readily be perceived as such (16).…”
Section: Resultssupporting
confidence: 92%
“…Direct comparisons of both markers in plants and animals have reported higher microsatellite variation than allozyme variation, but found inconsistent results with respect to genetic differentiation among populations. In wild rice, microsatellites detected higher genetic differentiation among populations (Gao et al 2002), whereas the opposite was found for Anopheles mosquitoes (Lehmann et al 1996).…”
Section: Fig 4 Genotype Assignment Tests Based On Cavalli-sforza's mentioning
confidence: 76%
“…In a population at MDE, both estimates should be equal (ie, H e ¼ H eq ). If (Lehmann et al, 1996;Zheng et al, 1996). All loci are located outside polymorphic chromosomal inversions 2La, 2Rb and 2Rd known to occur at very low frequencies in the Forest cytoform of A. gambiae s.s. (Coluzzi et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates are within the range of those found in A. gambiae mainland populations. Long-term N e values (IAM-SMM) around 6500-21 000 (Senegambia), 7500-23 000 (Western Kenya), 8500-24 000 (Gabon) and 11 500-49 000 (Cameroon) are derived by reanalysing microsatellite data in previous publications (Lehmann et al, 1996(Lehmann et al, , 1998Pinto et al, 2002;Wondji et al, 2002). In addition, present estimates of long-term N e may also be underestimated.…”
Section: J Pinto Et Almentioning
confidence: 92%